Young adult literature from romance to realism - Cart, Michael (IG library, 2010)
Today's young adult literature is every bit as complex as the audience it's written for, unflinchingly addressing such topics as homosexuality, mental illness, AIDS and drug abuse. In this much expanded revision of his 1996 book, veteran author Michael Cart shows how the best of contemporary YA lit has evolved to tackle such daunting subjects without resorting to sensationalism. He brings his historical survey of this category fully up to date, covering its explosive growth in the past decade, and advocating that librarians and teachers look beyond romance and horror when advising young adults.